VD_FINDINFO AI 284/20 - 194/2021 vom 1. Juli 2021 - VD Tribunal cantonal (2021)
BÉNÉFICIAIRE DE RENTE, FORCE PROBANTE, ÉTAT DE SANTÉ, MODIFICATIONEN GÉNÉRAL | 28 LAI, 4 al. 1 LAI, 17 LPGA, 6 LPGA, 7 LPGA, 8 al. 1 LPGA, 88a al. 1 RAI